Medical treatment of nocturia in men with lower urinary tract symptoms: systematic review by the European Association of Urology Guidelines panel for male lower urinary tract symptoms - Sakalis, Vasileios; Bach, Thorsten (European urology, 2017)
Context: The treatment of nocturia is a key challenge due to the multi-factorial pathophysiology of the symptom and the disparate outcome measures used in research. Objective: To assess and compare available therapy options for nocturia, in terms of symptom severity and quality of life. Evidence acquisition: Medical databases (Embase, Medline, Cochrane Systematic Reviews, Cochrane Central) were searched with no date restriction. Comparative studies were included which studied adult men with nocturia as the primary presentation and lower urinary tract symptoms including nocturia or nocturnal polyuria. Outcomes were symptom severity, quality of life, and harms. Evidence synthesis: We identified 44 articles. Antidiuretic therapy using dose titration was more effective than placebo in relation to nocturnal voiding frequency and duration of undisturbed sleep; baseline serum sodium is a key selection criterion. Screening for hyponatremia (< 130 mmol/l) must be undertaken at baseline, after initiation or dose titration, and during treatment. Medications to treat lower urinary tract dysfunction (α-1 adrenergic antagonists, 5-α reductase inhibitors, phosphodiesterase type 5inhibitor, antimuscarinics, beta-3 agonist, and phytotherapy) were generally not significantly better than placebo in short-term use. Benefits with combination therapies were not consistently observed. Other medications (diuretics, agents to promote sleep, nonsteroidal anti-inflammatories) were sometimes associated with response or quality of life improvement. The recommendations of the Guideline Panel are presented. Conclusions: Issues of trial design make therapy of nocturia a challenging topic. The range of contributory factors relevant in nocturia makes it desirable to identify predictors of response to guide therapy. Consistent responses were reported for titrated antidiuretic therapy. For other therapies, responses were less certain, and potentially of limited clinical benefit. Patient summary: This review provides an overview of the current drug treatments of nocturia, which is the need to wake at night to pass urine. The symptom can be caused by several different medical conditions, and measuring its severity and impact varies in separate research studies. No single treatment deals with the symptom in all contexts, and careful assessment is essential to make suitable treatment selection.
Available online 27 June 2017
Gesehen am 15.11.2018